Pengembangan Sistem Informasi Manajemen Penjualan Belimbing dan Olahannya (Studi Kasus : Kelompok Tani Blimbing Artha Mandiri) - Nur Anisa; Denny Sagita Rusdianto; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Blimbing Artha Mandiri Farmer Group is a community group having the same agriculture and having purposes to increase productivity, welfare for farmer members in one agricultural area. Blimbing Artha Mandiri Farmer Group is located in Tulungagung Regency with starfruit farming. In its development, farmer group has a problem in carrying out management of farmer group activity that still uses conventional methods, such as recording the selling of agricultural products to farmer group, then also registering farmer group members that is done by making people come bringing registration applications, then continued with checking applications and recorded in the members' recap book. While the difficulties are obtaining a list of benefits and financial recap of farmer group by recording the selling activity, incoming goods, and different orders and often create different financial data and recapitulation problems which later will be reported to the person in charge of the village head. Selling management information system can be a solution to the problem above. Selling data processing and group activities of farmer group become better, also get structured financial information and clear to minimize of having mistakes. This management information system is built using a prototyping softwafe development model and uses a codeigniter framework. The results of requirements manipulation get 59 functional requirements and 1 non-functional compatibility requirement. Designing has been done with 5 designs including, architectural design, sequence diagram, class diagram, component design, database design, and interface design. Then in the implementation step results component implementation, database implementation, and interface implementation. Testing has been done by using the whitebox testing method as a unit test, while the validation testing used blackbox testing by testing to 59 functional. Then non-functional testing was done by using compatibility testing. Results of 59 Functional tests using blackbox testing is obtained 100% valid results. Compatibility Test results, the system can run on Google Chrome browser and Mozilla Firefox.